ADAPTIVE AI FRAMEWORK FOR DYNAMIC SHARIA COMPLIANCE IN INDONESIAN ISLAMIC FINANCE: AN ETHICAL AND RELIGIOUS PERSPECTIVE - Ferdinand Salomo Leuwol; Sam Hermansyah; Abdul Wasik; Husna Amin; Sitti Nur Alam (CV. Adiba Aisha Amira, 2024)
This study explored the development and application of an adaptive AI framework for dynamic Sharia compliance within the Indonesian Islamic finance sector, all from an ethical and religious perspective. Our investigation was grounded in the historical evolution of Sharia compliance principles in Indonesia, recognizing the nuanced shifts and factors influencing these changes over time. We conducted an in-depth examination of the current landscape of AI in Islamic finance globally and assessed its adoption within the Indonesian context. We focused on how AI technologies can effectively address the challenges posed by the evolving interpretations of Sharia principles. The core of this research centered on developing a specialized AI-powered Sharia compliance framework. This framework was designed to be flexible and responsive to changes in Sharia regulations and principles, ensuring ongoing compliance while adhering to ethical and religious guidelines. We also scrutinized the ethical and religious implications of deploying AI in the Islamic finance sector, considering the perspectives of scholars, practitioners, and religious authorities. Additionally, we delved into the existing legal and regulatory framework surrounding AI applications in Indonesian Islamic finance. Our study featured case studies of Indonesian Islamic financial institutions that have adopted AI-driven compliance systems. These case studies provided valuable insights into the real-world impact of AI on ethical practices and religious adherence within the industry. Ultimately, our findings shed light on the potential of AI to facilitate dynamic Sharia compliance while adhering to ethical and religious principles, contributing to the ongoing growth and sustainability of Islamic finance in Indonesia.